Study of Living Hadith Towards Kubro Siswo Arts as Islamic Syi'ar - Ahmad Ubaidillah Ma'sum Al-Anwari; Bagus Wicaksono; Danang Wahyu Saputro (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2022)
Art is a medium of da'wah that grows and develops until now. Islam brought by the guardians to the archipelago has a basis on symbols, including symbols in art. If art is explored more deeply, it will be understood things that are closely related to religious texts. Kubro Siswo is the art of dance accompanied by music and syi'ir-syi'ir that contains advice. This art is not only limited to spectacle, but also demands that are conveyed through the syi'ir-syi'ir. Kubro Siswo is usually displayed in big events, such as the month of independence, Isra 'Mi'raj, and other events. The phenomenon of Kubro Siswo's art becomes very interesting to study. Based on the phenomenological theory, it will appear that this art has a considerable impact on the life of the Magelang community. This art not only functions as a spectacle that teaches love for ancestral traditions, but also as a means of da'wah that always invites people to cultural values that are in line with Islamic law. Every poem sung in Kubro Siswo's art has a deep meaning, which contains an invitation to goodness that is indirectly sourced from the Qur'an and Hadith.